EGFR mutations cause a lethal syndrome of epithelial dysfunction with progeroid features. Issue 5 (4th June 2015) - Ganetzky, Rebecca; Finn, Erin; Bagchi, Atrish; Zollo, Ornella; Conlin, Laura; Deardorff, Matthew; Harr, Margaret; Simpson, Michael A.; McGrath, John A.; Zackai, Elaine; Lemmon, Mark A.; Sondheimer, Neal
Abstract : We identified homozygous c.1283G>A (p.Gly428Asp) mutations in the extracellular domain of EGFR in two siblings. The children were born prematurely, had abnormalities in skin and hair, suffered multisystem organ failure and died in the neonatal period from intestinal perforation. In patient‐derived fibroblasts EGF failed to induce mutated receptor phosphorylation, activation of downstream targets was supressed and cells underwent early senescence. Abstract: The epidermal growth factor receptor (EGFR) is part of a large family of receptors required for communicating extracellular signals through internal tyrosine kinases. Epidermal growth factor (EGF) signaling is required for tissue development, whereas constitutive activation of this signaling pathway is associated with oncogenic transformation. We identified homozygous c.1283G>A (p.Gly428Asp) mutations in the extracellular domain of EGFR in two siblings. The children were born prematurely, had abnormalities in skin and hair, suffered multisystem organ failure, and died in the neonatal period from intestinal perforation. EGF failed to induce mutated receptor phosphorylation in patient‐derived fibroblasts and activation of downstream targets was suppressed. The heterologously expressed extracellular domain was impaired in stability and the binding of EGF. Cells from the affected patient undergo early senescence with accelerated expression of β ‐galactosidase and shortened telomeres at all passages when compared to controls. A comparison of homozygous inherited regions from a separate report of a patient from the same ethnic background and EGFR genotype confirms the pathogenicity of EGFR mutations in congenital disease.